2003
DOI: 10.7748/ns.17.31.41.s58
|View full text |Cite
|
Sign up to set email alerts
|

Travel advice for clients with pre-existing medical conditions

Abstract: Overseas travel, especially long-haul, can have risks that are not only associated with infection but also the mode of transport, climate, lifestyle and conditions at the destination. These risks may be magnified if the individual has a pre-existing medical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Most elderly travelers take several medications. In preparation for packing, extra quantities of each medication including frequently used over‐the‐counter medications and emergency medications, such as epinephrine pens, should be purchased to allow for lost or stolen luggage (Driver, 2003). This may be expensive and may cause the traveler to reconsider the destination or departure date.…”
Section: Preparing To Travelmentioning
confidence: 99%
See 2 more Smart Citations
“…Most elderly travelers take several medications. In preparation for packing, extra quantities of each medication including frequently used over‐the‐counter medications and emergency medications, such as epinephrine pens, should be purchased to allow for lost or stolen luggage (Driver, 2003). This may be expensive and may cause the traveler to reconsider the destination or departure date.…”
Section: Preparing To Travelmentioning
confidence: 99%
“…Each medication should be left in its original container with the manufacturer's name or pharmacy label, not in weekly medication planners, for easy identification by airport security and customs officials. Remind the traveler to pack all medications in the carry‐on luggage and not in the checked luggage in case the checked luggage gets lost (Driver, 2003). A letter signed by their primary HCP on official letterhead listing these medications and doses, as well as syringes if needed, should be taken along in case the medications are questioned by security or the traveler needs to seek care abroad.…”
Section: Preparing To Travelmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity level and climate effects can also affect insulin requirements. Driver (2003) found that regular blood glucose monitoring is crucial and the traveler must understand how to alter insulin intake based on the results. Gill and Redmond (1999) surveyed United Kingdom physicians who ran diabetic clinics and found that advice quality varied greatly and regimens were excessively complicated.…”
Section: Olabbtbsmentioning
confidence: 99%